THE EFFECTS OF HIGH TEMPERATURE HEATING ON COLOUR AND WEIGHT CHANGES IN GIC AND RMGIC (A STUDY TO SUPPORT IDENTIFICATION OF FIRE VICTIMS) - Nia Damayanti; Ira A. Kusuma; Tuntas Dhanardhono; Brigitta Natania (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: The temperature reached by fire disaster was varies. The disaster can cause fatalities and thus human identification is required. Dental restorative materials have properties that are resistant to high temperatures and play a role in identification process of fire victims. The identification process can be observed from the change in colour and weight of the restorative material. GIC and RMGIC are some of the most commonly used restorative material because they have good aesthetics properties, biocompatible, economical, and can release fluoride.  Purpose: To determine the effect of high temperature heating on colour and weight changes in GIC and RMGIC as a support for forensic identification. Method: A total of 30 GIC and RMGIC samples used in this study were made in the form of cylinder with a size 3x2 mm. Each material was heated at four temperature groups of 30°C-200°C, 30°C-400°C, 30°C-800°C dan 30°C-1100°C using a furnace. The study was continued with the examination of colour using the Vitapan Classical Shade Guide and weight changes using a digital scale. Results: GIC and RMGIC experienced changes in colour and weight changes due to hight temperatures of 30°C-200°C, 30°C-400°C, 30°C-800°C dan 30°C-1100°C. High temperature heating shows the difference of each material. This is indicated by the p value <0,001 in the Two Way Anova Test and Post Hoc LSD which means that there is a significant difference in weight difference between GIC and RMGIC at each temperature interval. Conclusion: High temperature heating affects the colour and weight changes of GIC and RMGIC.  Keywords: Forensic identification, GIC, High temperature heating, RMGIC